2017
DOI: 10.1080/19476337.2017.1302995
|View full text |Cite
|
Sign up to set email alerts
|

Profile analysis and correlation across phenolic compounds, isoflavones and antioxidant capacity during germination of soybeans (Glycine max L.)

Abstract: View related articles View Crossmark data Citing articles: 11 View citing articles Profile analysis and correlation across phenolic compounds, isoflavones and antioxidant capacity during germination of soybeans (Glycine max L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 48 publications
5
19
0
1
Order By: Relevance
“…This can be attributed to the de novo synthesis and transformation. Interestingly, an almost twofold increase in antioxidant capacity occurred, suggesting that germination generates new antioxidant compounds other than phenols, including an increase in vitamin content and the activation of the chlorophyll, which has high antioxidant capacity [41]. Finally, germination induces changes in the concentration of minerals, as was observed in calcium concentration of chia sprouts, probably as a consequence of an increase in its extractability [41].…”
Section: Discussionmentioning
confidence: 92%
“…This can be attributed to the de novo synthesis and transformation. Interestingly, an almost twofold increase in antioxidant capacity occurred, suggesting that germination generates new antioxidant compounds other than phenols, including an increase in vitamin content and the activation of the chlorophyll, which has high antioxidant capacity [41]. Finally, germination induces changes in the concentration of minerals, as was observed in calcium concentration of chia sprouts, probably as a consequence of an increase in its extractability [41].…”
Section: Discussionmentioning
confidence: 92%
“…Germinated seeds of Vitis californica contained 42.40-204.00 µg/g of fresh weight of gallic acid (Weidner et al, 2014). Soybean sample also showed improved level of quercetin (523.82-955.29 μmol/100 g) and catechin (38.38-159.95 μmol/100 g) after 6 days of germination, respectively (Guzmán-Ortiz et al, 2017).…”
Section: Hplc Phenolic Profilementioning
confidence: 97%
“…proved level of quercetin (523.82-955.29 μmol/100 g) and catechin (38.38-159.95 μmol/100 g) after 6 days of germination, respectively(Guzmán-Ortiz et al, 2017).…”
mentioning
confidence: 96%
“…Compared with the content of phenolics in other sprouts, our results showed that the amount of phenolics in illuminated chia microgreens (24 and 48 h) was higher or similar [7,38,39]. These variations could be attributed to the different enzymatic activity of hydrolases and polyphenol oxidases [40], de novo synthesis of phenolics, differences in polymerization and oxidation processes, and degradation of The increase of photosynthetic pigments in treated chia microgreens indicates the association between chlorophyll and carotenoid synthesis and the length of exposure to light.…”
Section: Effect Of Illumination Total Phenolic and Protein Contentmentioning
confidence: 52%